Verifying documentation form for Whistling Swan sighting submitted by Frederick Lesher, January 3 1981 - Lesher, Fredet al (1981)
A form submitted by Frederick Lesher documenting the sighting of a Whistling Swan, dated January 3, 1980 [1981?]. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1980-1981. Epson - sheet feed/flatbed